2006
DOI: 10.1007/s10577-006-1035-8
|View full text |Cite
|
Sign up to set email alerts
|

cDNA-based gene mapping and GC3 profiling in the soft-shelled turtle suggest a chromosomal size-dependent GC bias shared by sauropsids

Abstract: Mammalian and avian genomes comprise several classes of chromosomal segments that vary dramatically in GC-content. Especially in chicken, microchromosomes exhibit a higher GC-content and a higher gene density than macrochromosomes.To understand the evolutionary history of the intra-genome GC heterogeneity in amniotes, it is necessary to examine the equivalence of this GC heterogeneity at the nucleotide level between these animals including reptiles, from which birds diverged. We isolated cDNAs for 39 protein-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 58 publications
4
50
0
1
Order By: Relevance
“…This is consistent with the results of genome sequencing in the green anole lizard (Anolis carolinensis, ACA) [11]. Chromosomal size-dependent GC compartmentalization is unique to birds and other reptiles whose karyotypes consist of macro-and microchromosomes [12]. However, crocodile chromosomes are different from those of birds and turtles that have numerous indistinguishable microchromosomes, and the chromosome GC content is unknown in CNI.…”
Section: Introductionsupporting
confidence: 83%
“…This is consistent with the results of genome sequencing in the green anole lizard (Anolis carolinensis, ACA) [11]. Chromosomal size-dependent GC compartmentalization is unique to birds and other reptiles whose karyotypes consist of macro-and microchromosomes [12]. However, crocodile chromosomes are different from those of birds and turtles that have numerous indistinguishable microchromosomes, and the chromosome GC content is unknown in CNI.…”
Section: Introductionsupporting
confidence: 83%
“…The chromosome homologies were investigated among the three species, and the numbers of homologous chromosome segments were found to be 25 and 49 for chromosomes 1-7 and the Z chromosomes between the snake and chicken and between the snake and human, respectively. We had constructed a cytogenetic map of the Chinese soft-shelled turtle (Pelodiscus sinensis) with 92 cDNA clones (4,20), which revealed that the chromosomes have been highly conserved between the chicken and the turtle, with the six largest chromosomes being almost equivalent to each other. All of the data collectively suggest that the number of chromosome rearrangements that occurred between the snake and chicken was much more than that between the turtle and chicken.…”
Section: Resultsmentioning
confidence: 99%
“…Alligator and turtle genome sizes are Ϸ30% smaller than human, Ϸ50% larger than chicken, and only Ϸ12% larger than Anolis, whose genome size is close to the mean for nonavian reptiles. Unlike alligator genomes, the anole, painted turtle, and chicken contain a significant number of microchromosomes (7), which we expect would be gene rich as reported for chickens (8) and the softshelled turtle (9). In general, it is unknown how the macrochromosomes of reptiles differ from those of mammals (10) and those of the nonavian reptiles investigated here.…”
mentioning
confidence: 79%